2020
DOI: 10.1021/acsaelm.0c00384
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence of Spin Transfer Torque on Two-Dimensional Cobalt-Doped MoS2 Ferromagnetic Material

Abstract: The manipulation of two-dimensional (2D) ferromagnetic materials by spin current is emerging as the central theme of 2D spintronics research. A paradigm of spintronic devices, the spin Hall magnetoresistance (SMR) device, has been elucidated to obtain direct evidence of spin transfer torque (STT) on a three-dimensional (3D) ferromagnet. Here, we present pioneering results on the SMR effect in a 2D cobalt-doped MoS2/Ta van der Waals heterostructure, confirming the existence of STT by the magnetic-field angle de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…[30] By varying the coverage of the intercalated metal from low concentration to complete intercalation with the intercalated atoms occupying the octahedral vacancies between the two S layers, the magnetic properties can be tuned. In addition, experimental results have shown that CoMoS 2 present ferromagnetic properties with out-of-plane magnetization and Curie temperature T c around 100 K. [31] Herein, we propose that the bilayer TMDs can serve as an efficient platform for forming 2D multiferroic systems with intrinsic ME coupling, such as Co intercalated bilayer MoS 2 . The intercalated Co atoms not only introduce the magnetism but also induce ferroelectricity via formation of polar structure.…”
mentioning
confidence: 88%
“…[30] By varying the coverage of the intercalated metal from low concentration to complete intercalation with the intercalated atoms occupying the octahedral vacancies between the two S layers, the magnetic properties can be tuned. In addition, experimental results have shown that CoMoS 2 present ferromagnetic properties with out-of-plane magnetization and Curie temperature T c around 100 K. [31] Herein, we propose that the bilayer TMDs can serve as an efficient platform for forming 2D multiferroic systems with intrinsic ME coupling, such as Co intercalated bilayer MoS 2 . The intercalated Co atoms not only introduce the magnetism but also induce ferroelectricity via formation of polar structure.…”
mentioning
confidence: 88%
“…445,447 SMR effects have been clearly observed in bilayers of the insulating 2D magnet Co-doped MoS 2 and Ta. 448 As mentioned above, the spin currents inducing SOT can be generated not only by the SHE of a 3D material as Pt but also from SOC effects in 2DEGs at interfaces or surfaces. An interesting example is given by the theory by Dolui et al 444 of the SOT acting on CrI 3 in the bilayer CrI 3 /monolayer TaSe 2 heterostructure shown in Figure 40c.…”
Section: Spintronics: From Fundamentals To Devicesmentioning
confidence: 98%
“…445 , 447 SMR effects have been clearly observed in bilayers of the insulating 2D magnet Co-doped MoS 2 and Ta. 448 …”
Section: Spintronics: From Fundamentals To Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The SMR effect has been observed in a system consisting of the van der Waals compound MoS 2 doped with Co impurities and Ta. 11 However, experimental studies of the SMR effect in proper layered magnets are lacking so far, while a variety of studies on magneto-transport behavior in van der Waals magnetic compounds interfaced with HMs (Ta, Pt, and W) have been reported, highlighting the importance of such heterostructures for spintronic applications. 12−17 We note here that, till date, most of such interfaces are assembled by sputtering of a HM layer on top of the selected van der Waals material, even though their structural characterization is scarcely reported.…”
Section: ■ Introductionmentioning
confidence: 99%